Stopping anticoagulation for isolated or incidental subsegmental pulmonary embolism: the challenges and lessons from the STOPAPE RCT - Daniel Lasserson; Pooja Gaddu; Samir Mehta; Agnieszka Ignatowicz; Sheila Greenfield; Clare Prince; Carole Cummins; Graham Robinson; Jonathan Rodrigues; Simon Noble; Susan Jowett; Mark Toshner; et al. (Health Technology Assessment)
Background The increasing use of computed tomography pulmonary angiography to investigate patients with suspected pulmonary embolism has led to an increase in diagnosis of small subsegmental pulmonary embolism, which is rarely detectable with nuclear medicine-based imaging, the standard imaging modality prior to the development of computed tomography pulmonary angiography. The case fatality of pulmonary embolism has fallen in line with the increase in subsegmental pulmonary embolism diagnoses from computed tomography pulmonary angiography suggesting that we may be over-diagnosing pulmonary embolism (i.e. we may be diagnosing mild forms of pulmonary embolism which may not need any treatment). Given that full anticoagulation has significant side effects of bleeding and subsegmental pulmonary embolism was not commonly diagnosed previously with nuclear medicine imaging (and therefore left predominantly untreated prior to computed tomography pulmonary angiography scanning), there is growing equipoise about the value of full anticoagulation for patients with subsegmental pulmonary embolism. Methods We tried to undertake an open randomised trial with blinded end-point adjudication that recruited patients diagnosed with subsegmental pulmonary embolism without evidence of thrombus in the leg veins, termed ‘isolated subsegmental pulmonary embolism’. We allocated patients with isolated subsegmental pulmonary embolism to either continuing with at least 3 months of full-dose anticoagulation (standard care) or stopping anticoagulation completely, unless they had a temporary hospital admission where prophylactic (i.e. preventative doses) of anticoagulation is standard practice. In addition, we interviewed patients and clinicians about their views on stopping anticoagulation for isolated subsegmental pulmonary embolism which would be a substantial change from current practice. We planned to assess the accuracy of isolated subsegmental pulmonary embolism diagnoses from computed tomography pulmonary angiographies. Results The trial was stopped prematurely due to low recruitment. This was due to a combination of insufficient trial sites, problems with identifying patients who were suitable to be recruited at the time of acute assessment in hospital, the impact of COVID-19 on research infrastructure and a lower prevalence than had been predicted based on published studies. Our interview study showed that the intervention (i.e. changing practice to stopping treatment) is feasible, although there were concerns raised about safety, which a trial would be needed to address. We did not have sufficient trial participants to determine accuracy of initial isolated subsegmental pulmonary embolism diagnoses. Conclusion Although we were not able to answer the question of whether it is clinically effective and cost-effective to stop anticoagulating patients with isolated subsegmental pulmonary embolism, we developed a protocol which can be used by future trialists who can successfully attract funding to address this research question, which remains important and an ongoing uncertainty for clinicians and patients. Future work Trialists attempting to answer this research question should plan for longer recruitment times and ensure there is sufficient resource for a large number of recruiting centres. Limitations There were insufficient recruits to progress from the pilot phase to the full STOPAPE trial. Funding This synopsis presents independent research funded by the National Institute for Health and Care Research (NIHR) Health Technology Assessment programme as award number NIHR128073. Plain language summary Pulmonary embolism is a potentially serious condition, whereby blood clots cause a blockage of the blood supply to the lungs. However, small pulmonary embolisms may not cause any symptoms and may be found on scans performed for other reasons. In these situations, it is unclear whether treatment is required for the pulmonary embolism. These clots in smaller blood vessels away from the centre of the lungs (subsegmental pulmonary embolism) may be removed by the body’s own mechanisms for dissolving clots without needing medications. Anticoagulant medication (‘blood thinners’) are given to patients with pulmonary embolism to prevent future blood clots but we are not sure if the risks from these medications (bleeding, which can be life threatening) outweigh the benefits in patients with very small blood clots in the lungs. This is why we did the STOPAPE trial. Although we aimed to enrol 1466 patients in the trial with half getting usual care of anticoagulation and half getting no anticoagulation, we could not recruit patients quickly enough to the trial and, as a result, we could not continue with the STOPAPE study. There were two main reasons for stopping the STOPAPE trial. Firstly, we could not get enough hospitals to agree to join the study, mainly because research teams were concentrating on studies to help with the COVID-19 pandemic and could not help with STOPAPE as a result. Secondly, even at the hospital sites that did take part in STOPAPE, they found it hard to identify patients with small lung blood clots while delivering usual care for acute (sudden) illnesses. In the small number of patients we did recruit, we found that our trial expert radiologists (doctors who examine scans to find illnesses) disagreed with the radiologists at hospital sites and therefore more research is needed to help interpret scans looking for small lung blood clots.